IMPACT OF AGING AND STRESS ON THE PERIODONTAL HEALTH OF THE GERIATRIC POPULATION BEFORE AND AFTER PERIODONTAL TREATMENT IN OLD HOMES OF KARACHI, PAKISTAN - MUSHTAQUE , U; IQBAL , A; NAVEED , A; ALI , AA; SHAHZAD , E; ASLAM , I (Biological and Clinical Sciences Research Journal, 2024)
Age and stress-related periodontal diseases are prevalent in the geriatric population and continue to provide a significant epidemiological concern. Objective: To assess the impact of ageing and stress on the periodontal health of the senior population before and after periodontal treatment Method: A cross-sectional study was conducted between February and October 2023. Twenty-two senior patients aged 55 to 77 were selected through purposeful random sampling, excluding those unwilling or unable to participate. A semi-structured questionnaire, translated into the native language, assessed periodontal health using the Basic Periodontal Examination (BPE). Informed consent was obtained from participants, who were assured confidentiality and the right to withdraw. Data analysis was performed using SPSS version 23, employing mean and standard deviation for continuous data and frequency tables for categorized data. Cross-tabulation and significance testing were utilized to demonstrate associations. Results: The results of the prevailing cross-sectional study reveal that there exists an association between moderate to elevated levels of perceived stress and the manifestation of severe instances of periodontal disease. As per the study findings, periodontitis tends to afflict individuals across older adult age demographics. Conclusion: The study emphasised that stress and ageing are key risk factors for periodontal diseases, underlining the importance of addressing them during therapy. Consistent oral hygiene can prevent periodontitis in older adults.